THE IMPACT OF MATHIGON MEDIA ON STUDENTS' LEARNING OUTCOMES IN INTEGER OPERATIONS: A QUASI-EXPERIMENTAL STUDY - Tantri Indriani; Ihsanudin Ihsanudin; Etika Khaerunnisa (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Mathematics learning on integer topics often faces challenges, such as low learning outcomes due to abstract teaching methods and limited student engagement. To address this, interactive digital learning media like Mathigon may be used. This quasi-experimental study aims to assess the impact of Mathigon media on students' mathematics learning outcomes in integer operations. The study used a nonequivalent control group design with 64 seventh-grade students selected through purposive sampling. One class (n=32) was assigned as the experimental group, receiving instruction using Mathigon media, while the control group (n=32) was taught using traditional methods. A validated learning outcomes test was used as the instrument. The results, analyzed using an independent sample t-test, indicated a significant difference in learning outcomes between the experimental and control groups (p<0.05). The experimental group had an average score of 75.71, while the control group had an average of 65.00. Thus, Mathigon media significantly improved students' learning outcomes on integer topics. Pembelajaran matematika pada materi bilangan bulat masih menghadapi berbagai tantangan, seperti rendahnya hasil belajar siswa akibat metode pembelajaran yang abstrak dan keterbatasan keterlibatan siswa. Salah satu solusi untuk mengatasi permasalahan ini adalah dengan menggunakan media pembelajaran digital interaktif seperti Mathigon. Penelitian kuasi-eksperimental ini bertujuan untuk menilai pengaruh penggunaan media Mathigon terhadap hasil belajar matematika siswa pada materi operasi bilangan bulat. Penelitian ini menggunakan desain kelompok kontrol pretest-posttest yang tidak setara dengan sampel sebanyak 64 siswa kelas VII yang dipilih menggunakan purposive sampling. Satu kelas (n=32) dijadikan sebagai kelompok eksperimen yang diajarkan menggunakan media Mathigon, sedangkan kelompok kontrol (n=32) menggunakan metode pembelajaran tradisional. Instrumen yang digunakan adalah tes hasil belajar yang telah divalidasi. Hasil analisis menggunakan uji t sampel independen menunjukkan adanya perbedaan signifikan pada hasil belajar antara kelompok eksperimen dan kelompok kontrol (p<0.05). Rata-rata hasil belajar kelompok eksperimen adalah 75,71, sementara kelompok kontrol 65,00. Dengan demikian, dapat disimpulkan bahwa media pembelajaran Mathigon memiliki pengaruh signifikan terhadap hasil belajar matematika siswa pada materi operasi bilangan bulat.